Parâmetros fisiológicos de laranjeiras com Huanglongbing - Saccini, Vanessa Aparecida Villanova [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The huanglongbing (HLB) is considered one of the most severe diseases of citrus. Since its discovery in Brazil in 2004, it has caused serious damage to the citrus production and industry in the country, making vulnerable this important sector of the Brazilian agribusiness. This disease is caused by phloemrestricted bacteria. Typical symptoms of plants are mottled, yellow branches, and small deformed fruits. Infected trees show phloem obstructions, which can also affect photosynthesis and water relations. The symptoms of HLB may be masked by other symptoms generated from some diseases, moreover, such symptoms can be confused with some mineral deficiencies. The objective of this study was to investigate the effects of HLB in the photosynthetic process, stomatal conductance, transpiration, water potential and mineral content of the flowers, leaves and branches on orange trees [Citrus sinensis (L.) Osbeck, 'Valencia'], to determine the physiological responses in plants infected by the disease. The treatments consisted of healthy plants, plants asymptomatic patients and symptomatic diseased plants. Gas exchange and water relations were measured in December/2011 and March/2012. To estimate the rate of carbon assimilation (A), stomatal conductance (gs) and transpiration (E) were selected leaves 8-9 months old, but was avoided leaves with severe symptoms in symptomatic plants, these measurements were performed 8:00 a.m., 12:00 a.m. and 3:00 p.m. The leaf water potential (Ψf) was observed during two day periods, at 6:00 a.m. and 2:00 p.m. Nutritional assessments were carried out for six leaves and branches, with intervals of 30 days each, and the flowers were evaluated only in November/2011. The results showed that A was not affected by the disease, but gs and E decreased in symptomatic and asymptomatic diseased plants, in the second evaluation. There was a reduction in Ψf at 2:00 p.m. Once ...

O huanglongbing (HLB) é considerada a mais severa doença em citros, foi constatada no Brasil em 2004 e desde então tem causado sérios danos à citricultura do país, podendo colocar em risco esse importante setor do agronegócio brasileiro. A doença é causada por bactérias limitadas ao floema. Os sintomas típicos das plantas são mosqueamento, ramos amarelos, frutos deformados e pequenos. Obstruções no floema, comuns no processo infeccioso também podem afetar a fotossíntese e as relações hídricas. Os sintomas do HLB podem ser mascarados por outros sintomas gerados a partir de algumas doenças, além do mais, tais sintomas podem ser confundidos com algumas deficiências minerais. O trabalho teve como objetivo verificar os efeitos do HLB no processo fotossintético, condutância estomática, transpiração, potencial hídrico e no conteúdo mineral das flores, folhas e ramos, em plantas de laranja ‘Valência’, visando conhecer as respostas fisiológicas nas plantas infectadas pela doença. Os tratamentos consistiram em plantas sadias; plantas doentes assintomáticas e plantas doentes sintomáticas. As trocas gasosas e relações hídricas foram medidas em dez/2011 e mar/2012. Para a estimativa da taxa de assimilação de carbono (A), condutância estomática (gs) e transpiração (E) foram selecionadas folhas de 8 a 9 meses de idade, porém evitou-se folhas com sintomas severos nas plantas sintomáticas, essas medidas foram realizadas às 8:00, 12:00 e 15:00 h. O potencial da água das folhas (Ψf) foi medido às 6:00 e 14:00 h, foram selecionados ramos com três folhas cada. Foram realizadas seis avaliações nutricionais para folhas e ramos, com intervalos de 30 dias cada, e as flores foram avaliadas apenas em Nov/2011. Os resultados evidenciaram que, A não foi alterada pela doença, mas a gs e a E apresentaram redução em plantas doentes, sintomáticas e assintomáticas, na ...
Keywords: Cítricos; Laranja - Doenças e pragas; Plantas - Transpiração; Fotossíntese; Nutrientes; Minerais na nutrição de plantas; Bacterias fitopatogenicas; Orange